Total Synthesis and Functional Evaluation of Fourteen Derivatives of Lysocin E: Importance of Cationic, Hydrophobic, and Aromatic Moieties for Antibacterial Activity. Issue 47 (14th October 2016) - Kaji, Takuya; Murai, Motoki; Itoh, Hiroaki; Yasukawa, Jyunichiro; Hamamoto, Hiroshi; Sekimizu, Kazuhisa; Inoue, Masayuki
Abstract: Lysocin E (1 ) is a structurally complex 37‐membered depsipeptide comprising 12 amino‐acid residues with an N‐methylated amide and an ester linkage. Compound1 binds to menaquinone (MK) in the bacterial membrane to exert its potent bactericidal activity. To decipher the biologically important functionalities within this unique antibiotic, we performed a comprehensive structure‐activity relationship (SAR) study by systematically changing the side‐chain structures ofl ‐Thr‐1, d ‐Arg‐2, N‐Me‐d ‐Phe‐5, d ‐Arg‐7, l ‐Glu‐8, andd ‐Trp‐10. First, we achieved total synthesis of the 14 new side‐chain analogues of1 by employing a solid‐phase strategy. We then evaluated the MK‐dependent liposomal disruption and antimicrobial activity against Staphylococcus aureus by1 and its analogues. Correlating data between the liposome and bacteria experiments revealed that membrane lysis was mainly responsible for the antibacterial functions. Altering the cationic guanidine moiety ofd ‐Arg‐2/7 to a neutral amide, and the C7‐acyl group ofl ‐Thr‐1 to the C2 or C11 counterpart decreased the antimicrobial activities four‐ or eight‐fold. More drastically, chemical mutation ofd ‐Trp‐10 tod ‐Ala‐10 totally abolished the bioactivities. These important findings led us to propose the biological roles of the side‐chain functionalities. Abstract : What parts work best? Antibiotic lysocin E (1 ), a 37‐membered depsipeptide, binds to menaquinone in the bacterial membrane to exert its potent bactericidal activity (see figure). Comprehensive SAR studies of1 were performed by systematically changing the side‐chain structures. The key structural features for the antimicrobial activities were established to be the cationic functionalities atd ‐Arg‐2/7, the hydrophobic acyl group atl ‐Thr‐1, and the indole ring atd ‐Trp‐10.